STRATEGI KOMUNIKASI POLITIK DEDI HUMADI DALAM PEMILIHAN UMUM LEGISLATIF ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN ROKAN HILIR TAHUN 2014 - Arief Triawang; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Communication strategies in politics is one of the keys to a successful Legislative Candidates in winning the election . Indonesia is a unitary state which has the principles of democracy , the government carried out from the people, by the people, and returned to the interests of the people through legislative representation. In these circumstances, the present Legislative Candidates in response to the roles and functions as a connector and absorbing people's aspirations .While the methodology used in the preparation of this paper uses qualitative namely, conducting interviews with Dedi Humadi as legislative candidates, then collect data , organize and classify the data . While the analysis is descriptive that describes the steps of political communication strategies undertaken Dedi Humadi in the general election legislators Rokan Hilir 2014 .The theory used in this discussion is the theoretical positioning of Adman Nursal said communication strategy to enter the brain window voters to a contestant implies that reflects the excellence of the contestants competitors in the form of an associative relationship . Then Anwar Arifin theory which says that the forms of political communication strategy that is political rhetoric, public Relatios political, political propaganda, political agitation, political campaigns, and political marketing .Smith's work done through various programs Dedi Humadi not in vain. There are a few things that the strategy of political communication in the success of Dedi Humadi legislative elections, namely, First, first requests a political campaign with mass communication and interpersonal communication by raising relevant issues to be ' slogan ' . Second, expand the network by cooperating with community leaders, community organizations, or the personal approach ( emotional attachment ). Third, run individual campaigns and rallies. Fourth, to optimize the role of the media is to create banners , baleho , stickers and calendars . Fifth, do political imagery that aims to convince the public that Dedi Humadi different from the other candidates .Keywords : strategy , communication strategy of political , legislative 2014